DYNAMICS OF GLYCOPROTEINS DISTRIBUTION IN LUNGS OF GUINEA PIGS WITH EXPERIMENTAL ALLERGIC INFLAMMATION - Popko, S.S.; Yevtushenko, V.M. (World of Medicine and Biology, 2022)
At present, the question of the reaction of the components of the local link of the innate immunity of the respiratory system under conditions of allergic inflammation in most aspects remains open. The study was carried out on male guinea pigs (animals with experimental ovalbumin-induced airways allergic inflammation). Morphological changes were investigated in structural components of the lung. We have found that an increase in the number of PAS-positive goblet cells is accompanied by hypersecretion of mucus and surfactant, functional hyperactivity of type II pneumocytes and alveolar macrophages in the early stages of the development of airways allergic inflammation (p